A new look at the metal trap in the Kupferschiefer district using sulfur isotope microanalyses of pyrite and chalcopyrite - Yang Liu; Joseph M. Magnall; Alexander Rocholl; Sarah A. Gleeson; Hans-Martin Schulz; Michael Göthel (Mineralium Deposita, 2026)
The European Kupferschiefer Province contains multiple sedimentary rock hosted copper (SRC) deposits and has been mined for many centuries. The formation of the SRC deposits has been described by various genetic models, which primarily differ in terms of the timing of ore stage sulfide formation relative to host rock deposition (i.e., syn-genetic vs. epigenetic). In this study, samples from two drill cores in the Spremberg-Graustein Kupferschiefer deposit (eastern Germany) are described. The depositional paleoredox conditions for the Kupferschiefer (T1) organic rich mudstone unit have been reconstructed using whole rock analyses of redox-sensitive trace elements (RSTE; e.g., Mo, U, V). The strong enrichments in RSTE and high Mo/U ratios suggest that euxinic conditions prevailed in the water column in this part of the basin. Reflected light and scanning electron microscope (SEM) petrography help constrain key paragenetic relationships and sulfur isotope microanalyses of pyrite and chalcopyrite (secondary ion mass spectrometry; SIMS) have been used to reconstruct conditions of sulfide formation in the main host units. Notably, extensive pseudomorphic replacement of carbonate cement and feldspar clasts by ore stage sulfides is evidence that hydrothermal activity post-dated the formation of diagenetic phases and major compaction. Nevertheless, strongly negative δ 34 S values in pyrite (–58.3‰ to − 48.3‰) and chalcopyrite (–44.8‰ to − 34.5‰) indicate that reduced sulfur was derived from open system organoclastic sulfate reduction (OSR) in all units. The petrographic evidence of host rock replacement means the isotopic evidence of open system sulfate reduction cannot be explained by sulfide precipitation from early diagenetic pore fluids; rather, it could indicate (i) that bacteriogenic sulfur was derived from the replacement of diagenetic pyrite, or (ii) an external source of bacteriogenic sulfur, perhaps in the form of a low temperature sulfur rich brine. A review of compiled data from the Kupferschiefer district suggests that a combination of both of these sources could have contributed to the metal trap.

Using zircon trace element composition to assess porphyry copper potential of the Guichon Creek batholith and Highland Valley Copper deposit, south-central British Columbia - Robert G. Lee; Kevin Byrne; Michael D’Angelo; Craig J.R. Hart; Pete Hollings; Sarah A. Gleeson; Miguel Alfaro (Mineralium Deposita, 2021)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Effects of Lactobacillus casei Shirota ingestion on common cold infection and herpes virus antibodies in endurance athletes: a placebo-controlled, randomized trial - Michael Gleeson; Nicolette C. Bishop; Lauren Struszczak (European Journal of Applied Physiology, 2016)

Effect of acute exercise and hypoxia on markers of systemic and mucosal immunity - Ida S. Svendsen; Erlend Hem; Michael Gleeson (European Journal of Applied Physiology, 2016)

Impact of intensified training and carbohydrate supplementation on immunity and markers of overreaching in highly trained cyclists - Ida S. Svendsen; Sophie C. Killer; James M. Carter; Rebecca K. Randell; Asker E. Jeukendrup; Michael Gleeson (European Journal of Applied Physiology, 2016)

The influence of hydration status during prolonged endurance exercise on salivary antimicrobial proteins - Sophie C. Killer; Ida S. Svendsen; Michael Gleeson (European Journal of Applied Physiology, 2015)

The impact of intensified training with a high or moderate carbohydrate feeding strategy on resting and exercise-induced oxidative stress - Alex J. Wadley; Sophie C. Killer; Ida S. Svendsen; Michael Gleeson (European Journal of Applied Physiology, 2015)

Influence of CMV/EBV serostatus on respiratory infection incidence during 4 months of winter training in a student cohort of endurance athletes - Cheng-Shiun He; Michal Handzlik; Ayu Muhamad; Michael Gleeson (European Journal of Applied Physiology, 2013)

The return of groundwater quantity: a mega-scale and interdisciplinary “future of hydrogeology”? - Tom Gleeson; Michael Cardiff (Hydrogeology Journal, 2013)

The influence of exercise training status on antigen-stimulated IL-10 production in whole blood culture and numbers of circulating regulatory T cells - Michal K. Handzlik; Andrew J. Shaw; Maurice Dungey; Nicolette C. Bishop; Michael Gleeson (European Journal of Applied Physiology, 2013)

Changes in natural killer cell subpopulations over a winter training season in elite swimmers - Luís Rama; Ana Maria Teixeira; Alice Matos; Grasiely Borges; Ana Henriques; Michael Gleeson; Susana Pedreiro; Edith Filaire; Francisco Alves; Artur Paiva (European Journal of Applied Physiology, 2013)

Cytokine production by monocytes, neutrophils, and dendritic cells is hampered by long-term intensive training in elite swimmers - José Mário Morgado; Luís Rama; Isabel Silva; Maria de Jesus Inácio; Ana Henriques; Paula Laranjeira; Susana Pedreiro; Fátima Rosado; Francisco Alves; Michael Gleeson; Maria Luísa Pais; Artur Paiva; et al. (European Journal of Applied Physiology, 2012)

Post-exercise protein synthesis rates are only marginally higher in type I compared with type II muscle fibres following resistance-type exercise - René Koopman; Benjamin G. Gleeson; Annemie P. Gijsen; Bart Groen; Joan M. G. Senden; Michael J. Rennie; Luc J. C. van Loon (European Journal of Applied Physiology, 2011)

The influence of prolonged cycling on monocyte Toll-like receptor 2 and 4 expression in healthy men - Marta Oliveira; Michael Gleeson (European Journal of Applied Physiology, 2010)

Salivary antimicrobial peptides (LL-37 and alpha-defensins HNP1–3), antimicrobial and IgA responses to prolonged exercise - Glen Davison; Judith Allgrove; Michael Gleeson (European Journal of Applied Physiology, 2009)

Small shifts in diurnal rhythms are associated with an increase in suicide: The effect of daylight saving - Michael BERK; Seetal DODD; Karen HALLAM; Lesley BERK; John GLEESON; Margaret HENRY (Sleep and Biological Rhythms, 2008)

Interoperability of Neuroscience Modeling Software: Current Status and Future Directions - Robert C. Cannon; Marc-Oliver Gewaltig; Padraig Gleeson; Upinder S. Bhalla; Hugo Cornelis; Michael L. Hines; Fredrick W. Howell; Eilif Muller; Joel R. Stiles; Stefan Wils; Erik De Schutter (Neuroinformatics, 2007)

Response to Hemilä - Michael Gleeson; Glen Davison (European Journal of Applied Physiology, 2007)

Elevated plasma interleukin-6 levels in trained male triathletes following an acute period of intense interval training - Paula J. Robson-Ansley; Andrew Blannin; Michael Gleeson (European Journal of Applied Physiology, 2007)

The effect of 2 weeks vitamin C supplementation on immunoendocrine responses to 2.5 h cycling exercise in man - Glen Davison; Michael Gleeson (European Journal of Applied Physiology, 2006)

The effects of carbohydrate supplementation during the second of two prolonged cycling bouts on immunoendocrine responses - Tzai-Li Li; Michael Gleeson (European Journal of Applied Physiology, 2005)

Effect of exercise-induced muscle damage on the blood lactate response to incremental exercise in humans - Michael Gleeson; Andrew K. Blannin; Neil P. Walsh; Christine N. E. Field; Jeanette C. Pritchard (European Journal of Applied Physiology, 1998)